The Influence of Role Ambiguity and Workload Moderated by Resilience on Employee Burnout - Ahmad Fadli; Muhammad Imam Muttaqijm; Muljadi Muljadi (PT Mattawang Mediatama Solution, 2024)
The purpose of this research is to determine the effect of Role Ambiguity, Workload moderated by Resilience on employee Burnout at PT. United Waru Biscuits manufacturing. Cikande Branch. The research method used is associative with a quantitative approach. Data collection techniques, data questionnaires and literature study. The partial research results of the first test using a one sample t-test showed; The first test of the Ambiguity variable on Burnout obtained a t-count value of 11.983 > t-table 1.988, with a significance of 0.000 < 0.05, this shows that there is a positive and significant influence, the second test of the Workload variable on Burnout obtained a t-count value of 6.813 > t -table 1.988 with a significance of 0.000 < 0.05, this shows that there is a positive and significant influence, the third test of Role Ambiguity on Employee Burnout which is moderated by Resilience obtained a t-count value of 1.045 < t-table 1.988, with a significance of 0.299 > 0, 05 This shows that there is no positive and significant influence. The fourth test of Workload on Employee Burnout moderated by Resilience obtained a t-count value of 1.695 < t-table 1.988, with a significance of 0.094 > 0.05, this shows that there is no positive and significant influence.